An Analysis of the Roles of Sakka Devarāja (Sakka, King of Devas) in Recent Theravāda Buddhist Societies in South-East Asia - Hoolahan, Mark Francis (The Journal of International Buddhist Studies College, 2023)
The main objective of this article, which is a qualitative literature-based one, is to analyze the roles of Sakka Devarāja in recent Theravāda Buddhist societies in South-east Asia in terms of his textual history as Vedic and post-Vedic Indra and Buddhist Sakka. The research indicates that Sakka Devarāja is a persistent and influential figure who continues to manifest in Thailand, Myanmar, Laos and Cambodia. Moreover, his roles in these recent Buddhist societies can be well understood in terms of his historical and textual ‘mythical background’ as Indra and Sakka.